BIMBINGAN BAHASA ARAB TINGKAT DASAR PADA MASYARAKAT KELURAHAN BENTENG CIAMPEA BOGOR - Muh. Abrar; Asriani (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
For ordinary people to see Arabic as a language that is difficult and difficult to understand. This happens because of the lack of effort to teach Arabic at the beginner level who is new to Arabic. Usually, the general public learns Arabic, which is complete with its meaning and meaning, making it focus on translation, not on the pronunciation of the language. Circumstances like this make language learners do not fully understand the meaning and meaning of the verse, and many of them even misunderstand the verse according to its true meaning. This situation encourages the servant to provide assistance in teaching Arabic at the basic level with the aim that the community where the service is held can understand the meaning of the contents of the Qur'an easily and correctly. At this stage of activity the servant carried out two methods, namely lectures and questions and answers. The data collection technique was carried out by direct face-to-face meetings between the servant and the community. Of course, the main target of this service is to see the community being able to interpret every verse that is read, moreover to appreciate and animate the text of the verses of the Koran that are read. Even more interpret every worship they do. All of this certainly has a positive effect on the community for teaching Arabic.